Peran Home Industry Dalam Meningkatkan Pendapatan Rumah Tangga: Studi Pada Home Industry Keripik Kentang Di Kecamatan Paal Merah Kota Jambi - Muhammad Hisyam; Miftah Miftah; Ahmad Syahrizal (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
This study aims to determine the role of the home industry in increasing household income (a study on the potato chip home industry in Paal Merah District, Jambi City). This research is qualitative in nature. Qualitative research is research that tends to use analysis with an inductive approach and is descriptive or explanatory in nature. This research focuses more on facts that occur in the field. The subjects of this study were home industry owners in the Paal Merah sub-district, Jambi city, employees who worked and providers of raw materials for the home industry. The data obtained comes from observations, interviews and documentation. The results showed that: First, the home industry in Paal Merah sub-district, Jambi city, has a positive impact on improving the household economy where welfare indicators can be seen from the role, income, and welfare of owners, raw material providers and employees who can set aside income from the results of work so that they can send their children to a better education, besides being used to meet daily needs can also help the head of the household in meeting other daily needs, Second, the existence of a home industry in Paal Merah sub-district, Jambi city, also plays a role in assisting the government in reducing poverty and reducing the number of unemployed in society, with the absorption of labor, especially housewives who are around to make the best use of their time, of course. will be able to help generate income for households, and in carrying out business activities food needs can be fulfilled properly and in accordance with Islamic teachings, then all business activities are protected and cared for during production activities, and can be used to meet needs in the future. Third, with the results of this research, it is hoped that the regional government, especially the province of Jambi, which is related to the development of Small and Medium Enterprises, will pay more attention to the existence of home industries in the Paal Merah sub-district, Jambi City, their business can increase and be able to compete in the market, of course it will also prosper the economy. small society.